Development of Hybrid Fibre Ferrocement Panels as Permanent Formwork of Concrete Slabs with Lightweight Blocks Infill - Abushawashi, Nadim Frhat (Curtin University, 2015)
The structural performance of ferrocement has been enhanced by using hybrid PV A fibre reinforcement. The improvement of the matrix toughness by the addition of hybrid PVA fibre enhanced the overall structural performance of the composite. The hybrid fibre reinforced ferrocement panels were then used as permanent formwork of reinforced concrete slabs with AAC-block as infill material. The developed slabs showed full composite action and the hybrid ferrocement panels functioned as permanent formwork.